2008 IEEE International Conference on Communications 2008
DOI: 10.1109/icc.2008.840
|View full text |Cite
|
Sign up to set email alerts
|

Fountain Coding with Decoder Side Information

Abstract: Abstract-In this contribution, we consider the application of Digital Fountain (DF) codes to the problem of data transmission when side information is available at the decoder. The side information is modelled as a "virtual" channel output when original information sequence is the input. For two cases of the system model, which model both the virtual and the actual transmission channel either as a binary erasure channel or as a binary input additive white Gaussian noise (BIAWGN) channel, we propose methods of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…But how close can we get to this lower bound? As shown in [13,14], standard LT and Raptor codes are not able to make any use of the partial information, and would require that each receiver receives slightly more than k encoding packets, to correctly recover entire message, which is very inefficient, especially for small p. However, slight modification of LT and Raptor codes is able to perform much better, as we demonstrate in the rest of this section.…”
Section: Coding With Partial Informationmentioning
confidence: 88%
See 2 more Smart Citations
“…But how close can we get to this lower bound? As shown in [13,14], standard LT and Raptor codes are not able to make any use of the partial information, and would require that each receiver receives slightly more than k encoding packets, to correctly recover entire message, which is very inefficient, especially for small p. However, slight modification of LT and Raptor codes is able to perform much better, as we demonstrate in the rest of this section.…”
Section: Coding With Partial Informationmentioning
confidence: 88%
“…Even though it has been demonstrated that the universal code parameters generally do not exist for noisy channel models [9], fountain codes have shown promising performance over channels such as binary input additive white Gaussian noise channel (BIAWGNC) [9] and block-fading channels [8]. In addition, fountain codes have been used in the context of lossless data compression [10], distributed source coding [11,12,13,14,15], distributed joint sourcechannel coding [16,17,18], transmission of scalable video [19,20,21,22] and transmission of multiple independent sources in relay networks [23].…”
Section: Fountain Codingmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution Ω( ) is called the output degree distribution, since it determines the degrees of the output nodes in the decoding graph. The output degree distribution is usually written in the generating polynomial notation 1…”
Section: B Lt Codes and Output Degree Distributionsmentioning
confidence: 99%